Effects of Feedback on Self-Assessment - Marion Eberlein; Sandra Ludwig; Julia Nafziger (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
It is a well-known phenomenon that people tend to overestimate their relative abilities. Psychological studies show that a vast majority of people thinks that their ability is above the average when they have to assess their position in a distribution of a target group. We analyse in an experiment whether this is still true when people receive feedback on their relative abilities. Our main finding is that feedback influences agent?s decisions and improves overall self-assessment.
Keywords: D01; C91; D80; 330; Overconfidence; Feedback; Experimental Economics